IMPROVING THE QUALITY OF EDUCATION IN THE DIGITAL ERA - Loso Judijanto; Rinda Riztya; Natal Kristiono (International Journal of Teaching and Learning, 2025)
In the digital era, the integration of technology in the educational process is important to improve the quality of learning. This article explores how technology can be used to support wider access and more effective learning, as well as the challenges that need to be overcome to achieve optimal educational quality. Technology allows access to diverse educational resources and interactive teaching methods that can be tailored to students' individual needs and potential. However, truly harnessing the benefits of technology presents some challenges. Key issues include equal access to devices and the internet, the need for ongoing training for teachers, the security and privacy of student data, the importance of maintaining a balance between digital learning and social interaction, and the need for continuous evaluation of the impact of technology on learning outcomes. With a comprehensive and adaptive approach, as well as attention to these critical aspects, the implementation of technology in education can contribute significantly to creating an education system that is inclusive, effective and relevant to the needs of the times. This article concludes that continuous innovation and adaptation are the main keys to exploiting the full potential of technology in improving the quality of education in the digital era.